Immunocytochemistry Evaluation of Fibroblast Response to Garlic (Allium sativum) Extract Targeting MMP9: In Vitro and In Silico Approaches - Ningsih, Sri Suciati; Zuraidah, Endah; Handayani, Supri Irianti; Ardiansyah, Ahmad Ali Irfan; Wahyuni, Ningrum (Indonesian Journal of Medical Chemistry and Bioinformatics, 2025)
Background: Fibrosis involves excessive extracellular matrix (ECM) deposition, with matrix metalloproteinase-9 (MMP-9) playing a critical role. Natural compounds targeting MMP-9 may offer therapeutic potential. Objective: This study evaluated the antifibrotic effect of Allium sativum extract on fibroblast cells through in vitro and in silico approaches targeting MMP-9. Methods: Human dermal fibroblasts were treated with A. sativum extract (25, 50, and 100 µg/mL) for 24 and 48 hours. Cell viability was assessed using MTT assay. MMP-9 expression was analyzed via quantitative real-time PCR (qRT-PCR) and immunocytochemistry (ICC). Major garlic compounds were docked to MMP-9 using AutoDock Vina. Results: The 50 µg/mL concentration maintained >85% cell viability and significantly reduced MMP-9 gene and protein expression. S-allyl cysteine exhibited the strongest binding affinity (−6.8 kcal/mol) and formed hydrogen bonds with key residues (Glu402, Ala189, His405) of MMP-9. Conclusion: Allium sativum extract demonstrates antifibrotic activity by downregulating MMP-9 expression and inhibiting its function, supporting its potential as a natural MMP-9 inhibitor for fibrosis-related disorders.